The susceptibility of hepatic collagen to homologous collagenase in human and experimental cirrhosis of the liver. - Pérez-Tamayo, R. (1980)
The susceptibility of hepatic collagen to homologous collagenase in human and experimental CCl4 cirrhosis of the liver has been explored in vitro by exposure of cryostat liver sections to the corresponding enzymes for different time periods. The morphology and extent of collagen degradation was studied by the Picrosirius red/polarizing microscopy technique. The results of various experiments indicate that collagen present in cryostat sections of both human and rat normal and cirrhotic livers is resistant to trypsin digestion for periods of exposure of up to 48 hours but that heating the sections to 60 C for 1 hour renders the collagen susceptible to degradation by trypsin. Incubation of cryostat liver sections with bacterial collagenase revealed progressive degradation of collagen with a uniform pattern of changes in the original color and diameter of the fibers. Exposure of liver sections to homologous collagenases gave rise to the same pattern of changes observed with bacterial collagenase, although less extensive when equal incubation periods were compared. Nevertheless, sufficiently prolonged incubation of liver sections with their homologous collagenases eventually showed degradation of all collagen present in all normal and cirrhotic liver sections. These observations suggest that in the presence of non rate-limiting concentrations of homologous collagenase, the susceptibility of hepatic collagen to the corresponding degrading enzyme is probably not responsible for the irreversibility of the disease.